2014
DOI: 10.1007/s11064-014-1417-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the Thioredoxin System, Glutathione Peroxidase Activity and Total Antioxidant Capacity in Rat Brain Cortex During Acute Liver Failure: Modulation by l-histidine

Abstract: Glutathione and thioredoxin are complementary antioxidants in the protection of mammalian tissues against oxidative–nitrosative stress (ONS), and ONS is a principal cause of symptoms of hepatic encephalopathy (HE) associated with acute liver failure (ALF). We compared the activities of the thioredoxin system components: thioredoxin (Trx), thioredoxin reductase (TrxR) and the expression of the thioredoxin-interacting protein, and of the key glutathione metabolizing enzyme, glutathione peroxidase (GPx) in the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…2 ). In agreement with earlier reported data [ 26 ], the total antioxidant capacity (TAC) in brain homogenates from TAA rats was increased by ~50 %. While administration of His or Car did not affect TAC in control brains, each potentiated TAC in TAA -affected brain (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…2 ). In agreement with earlier reported data [ 26 ], the total antioxidant capacity (TAC) in brain homogenates from TAA rats was increased by ~50 %. While administration of His or Car did not affect TAC in control brains, each potentiated TAC in TAA -affected brain (Fig.…”
Section: Resultssupporting
confidence: 92%
“…However, His is also known for its antioxidant action [ 23 , 24 ]. Moreover, studies from our laboratory have shown that His also prevents reduction of glutathione content in brain mitochondria of TAA rats [ 25 ] and increases the total antioxidant capacity (TAC) of TAA rat brain [ 26 ]. In the same TAA model of HE, intraperitoneal (i.p.)…”
Section: Introductionmentioning
confidence: 99%
“…His was suggested to exert these effects by inhibiting mitochondrial Gln transport. Alternatively, the protective properties of His could be due to its antioxidative potential of this amino acid as noted both in the central nervous system (CNS) and in non CNS tissues in different conditions (Wade and Tucker, 1998), and recently confirmed in the TAA model of HE (Ruszkiewicz and Albrecht, 2014;Ruszkiewicz et al, 2013). The decrease of ADMA concentration evoked by His in TAA rat model of ALF could be most likely due to one, or the combination, of the following events: (i) changes in DDAH activity and/or expression, (ii) inter-cellular or blood-brain barrier ADMA transport.…”
Section: Article In Pressmentioning
confidence: 94%
“…Thus, in vitro data on the redox exchange between mitochondrial thioredoxin and the complex-bound dihydrolipoyl residues are supported by the consequences of genetic or pharmacological manipulations affecting cellular redox state and viability. As shown in the next sections, the interaction of the dihydrolipoyl residues with thioredoxin may transmit the signal on perturbed homeostasis from the 2-oxo acid dehydrogenase complexes to thiol-based peroxidases (peroxiredoxins) and a thioredoxin-interacting protein regulating mitochondrial function in mammals (164,212).…”
Section: B Complex-bound Dihydrolipoyl Residues Reduce Thioredoxinmentioning
confidence: 99%